2020
DOI: 10.3390/geosciences10040124
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Storage Changes Derived from GRACE and GLDAS on Smaller River Basins—A Case Study in Poland

Abstract: In the era of global climate change, the monitoring of water resources, including groundwater, is of fundamental importance for nature, agriculture, economy and society. The purpose of this paper is to check compliance of changes in groundwater level obtained from direct measurements in wells with groundwater storage (GWS) anomalies calculated using gravity recovery and climate experiment (GRACE) observations in Poland. Data from the global land data assimilation (GLDAS), in the form of soil moisture (SM) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…The KBRR inversion using SF for both cases of the Congo and Nile basins, yield results that are very comparable with those of the GLDAS model for frequency (temporal variations) and latitudinal zonation (spatial variations). In terms of intensity, a relatively constant and clear bias is observed like many authors have observed before (in South America [37], Africa [38], Poland [39], and at global scale [40]) and it corresponds, in our case, to a factor~2. So, in order to be able to compare the estimated SF maps, we have chosen to divide the outputs of the GLDAS simulation by 2, at least to ease the graphical representation using the same color scale (Figure 3).…”
Section: Analysis Of the Slepian Coefficient Truncationsupporting
confidence: 88%
“…The KBRR inversion using SF for both cases of the Congo and Nile basins, yield results that are very comparable with those of the GLDAS model for frequency (temporal variations) and latitudinal zonation (spatial variations). In terms of intensity, a relatively constant and clear bias is observed like many authors have observed before (in South America [37], Africa [38], Poland [39], and at global scale [40]) and it corresponds, in our case, to a factor~2. So, in order to be able to compare the estimated SF maps, we have chosen to divide the outputs of the GLDAS simulation by 2, at least to ease the graphical representation using the same color scale (Figure 3).…”
Section: Analysis Of the Slepian Coefficient Truncationsupporting
confidence: 88%
“…Frappart and Ramillien [60] also found that these data were used to evaluate the parameters; the specific yield, for example, is used to relate groundwater level to storage or to describe the indices of groundwater depletion and stress. In another GRACE-GLDAS study, it was found that high consistency exists between GRACE observations and changes in water wells [119].…”
Section: Grace Applicationsmentioning
confidence: 95%
“…GLDAS soil moisture data have been largely used by regional and global analyses of water budget, presenting satisfactory estimations (e.g. Bi et al, 2016;Rzepecka & Birylo, 2020;Sazib et al, 2018;Spennemann et al, 2015). Also, it covers the longest period of data availability among the soil moisture products available on the Google Earth Engine (GEE) database.…”
Section: Soil Moisture Storagementioning
confidence: 99%